OCCUPATIONAL MENTALITY DEVELOPMENT FOR WORK IN HAZARDOUS CONDITIONS - Bessonova, Yu.V. (Modern Psychology, 2019)
Occupational mentality plays a key role in ensuring job efficiency and reliability on the human factor. The occupational mentality has a special importance for extreme work in hazardous labor conditions. Job efficiency hasn’t correlation with labor experience and age, but it reflects the mentality to work. The mentality has similarities in different extreme occupations determined by the job requirements and conditions. A comparative analysis of different age groups reflects the development of specific mentality to persons who have worked for not less than 7 years.